IMPLEMENTASI KESELAMATAN LALU LINTAS PADA ANAK USIA DINI DENGAN METODE PENDEKATAN PEMBELAJARAN KOOPERTAIF TIPE ROLE PLAYING - alfian saleh (Universitas Lancang Kuning, 2018)
The disciplined person can not be formed instantaneously, nor in the form of traffic discipline. Traffic education for early childhood is one way of preventing traffic accidents that can be planted early on. Safety education activities are part of community service conducted to students of kindergarten Alifa Kids 5. Community service is part of Tridharma Perguruan Tinggi. This activity aims to increase students' knowledge about safety in schools, especially regarding safety signs. Commander of the community is a method of implementation of this communit in the form of education followed by questions and answers and roleplay. This activity is done by cooperative method of role playing type where every student of student switch role become a role in this thing that is procedure of crossing. The result of this activity is student of kindergarten Alifa Kids 5 can play role in case crossing highway. The conclusion of this activity is the increase of students' knowledge about implementing traffic safety especially crossing the road. It is hoped that with increasing and implementing procedures to cross the right path can raise students' awareness for safe behaviors increase.. Keywords: Crossing the Road, Safety Education, Role Playing